Aplikasi Pembukuan Keuangan Bendahara Pengeluaran Universitas Andalas dengan Menggunakan Bahasa Pemograman PHP - Kurniawan, Kurniawan; Suhendri, Ade Putra Prima; Putra, Ilham Eka; Junaidi, Junaidi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Progress of information technology at the moment continue to expand along with requirement of human being wishing amenity, accuracy and speed in obtaining information. One of them impact on the advancement of information technology in the field of financial accounting. Andalas University is a leading Educational Institutions. To carry out the activity of many lectures at the University of Andalas perform various financial data processing. Bookkeeping treasurer computer using the media as a tool to perform data processing using Microsoft Excel. Leaders so difficult to get reports more quickly and accurately. In this case I use the PHP programming language and MySQL are useful to help process the financial accounting data treasurer Andalas University. PHP programming language which is connected to the database is very helpful in the process of financial accounting data processing treasurer. So the reports in financial accounting data processing treasurer avoid mistakes, faster and more accurate.